Recent research on Brent Geese - Boyd, Hugh (Wildfowl, 1959)
For many years the status of the Brent Goose (Branta bernicla (L.)) has caused concern because of a marked decline in numbers in most parts of its range. Strenuous efforts by bird protection organizations in most countries of north-western Europe intended to obtain or increase legal protection for the species have achieved some success and have been accompanied by detailed investigations into the present and past distribution of the bird. The first part of this review consists of an abstract of a lengthy report on the status of Brent in Europe by Dr. Finn Salomonsen, published late in 1958.